PENGEMBANGAN PERANGKAT PEMBELAJARAN KOOPERATIF PADA BIOLOGI PERKEMBANGAN HEWAN - M. HAVIZ; Lufri Lufri; Helendra Helendra; Ramadhan Sumarmin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
This research focused on developing cooperative learning materials for biology of animal growth. This research therefore aimed designing teaching instructional, testing validity and testing practicality of the implementation of the materials upon the topic of animal growth in biology. This research employed research and development design. The first phase dealt with reconstruction or designing learning materials and the instrument that were used in cooperative learning. Next, testing instrument validity was done by expert. In the last phase, limited try out was conducted to figure out the practicality. The findings showed that learning materials and the supporting instruments were valid. Such learning materials included syllabus, lesson plans, students’ lab sheets, concept map manual and students’ achievement evaluation sheet. Implementation practicality was assessed from the cooperative learning process and students’ responses. The findings showed that the learning process was suitable with prepared syllabus and lesson plans, and students’ responses toward learning process was in good category.Kata kunci: pembelajaran kooperatif, perangkat, instrumen, biologi perkembangan hewan